Rancangan Persediaan Bahan Baku Produk Engsel Untuk Mengefisiensikan Biaya Proses Produksi - Mochammad Basjir; Suhartini Suhartini (Fakultas Teknik, 2022)
PT. ABC is a manufacturing company producing machinery in the agricultural, plantation, and marine sectors. Currently, the product that is the focus to be produced by PT. ABC includes three types, namely Machining Center, Shipyard, and Diesel Engine, distributed by the selling distributor company, namely PT. Rutan is also a subsidiary of PT. A B C. One of the main spare parts for these machines is hinge products that the company produces. This study will use the EOQ (Economic Order Quantity) method in planning the inventory level of the hinge product raw materials by minimizing the total storage cost and ordering cost. This study aims to determine and minimize the inventory cost of raw materials issued by the company. The analysis results obtained the calculation of the value of the inventory cost of raw materials that the company must issue based on the policies that have been used within one year of Rp. 6,823,023 with an order frequency of 12 times and an average order of 4.273 times. Meanwhile, using the EOQ (Economic Order Quantity) method approach, the total value of inventory costs that the company must incur during one year is Rp. 3,244,994 with an order frequency of 5 times and the average value of ordering 10,272 times.